Formation and training of stunting cadres in Pulau Sarak Village, Kampar Regency - Rusherina Rusherina; Kurniawati Kurniawati; Idayanti Idayanti (Universitas Muhammadiyah Magelang, 2022)
A child who is stunted has malnutrition and is underweight, as evidenced by their height falling below the WHO standard. Stunting is brought on by a deficiency in nutrition during the first 1000 days of life. Stunting impedes not only physical growth but also the brain development. One of the villages in Kampar Regency, which is the location for handling stunting interventions in Riau Province, is Pulau Sarak Village. The purpose of this activity is to form and train stunting cadres. The method of implementing this program begins with the formation of cadres and continues with training on early stunting detection in children aged 0-24 months for 25 cadres. The results of these activities were the formation of stunting cadres and increased knowledge of cadres about stunting prevention in Pulau Sarak Village, Kampar Regency with an average value of pre-test (80.94) and post-test (91.44), resulting in an increase of 10.64. In order to prevent stunting occurrences in Pulau Sarak Village, Kampar Regency, it is advised that cadres be able to weigh and monitor growth and development on a regular basis (at least once a month).